Geochemistry and Fluid Inclusions Analysis of Vein Quartz in the Multiple Hydrothermal Systems of Mankayan Mineral District, Philippines. Issue 1 (3rd September 2019) - Manalo, Pearlyn C.; Subang, Leo L.; Imai, Akira; de los Santos, Mervin C.; Takahashi, Ryohei; Blamey, Nigel J. F.
Abstract: Several high‐sulfidation epithermal gold orebodies in the Mankayan Mineral District were formed in an environment that has been already affected by earlier porphyry‐type mineralization. This study reports the geologic and geochemical characteristics of the Carmen and Florence epithermal orebodies, which are located in the south of the Lepanto main enargite–gold orebody. The gold‐bearing epithermal quartz veins in the Carmen and Florence areas are of two types: (i) the enargite‐rich veins and (ii) the quartz–pyrite–gold (QPG) veins. The two types of veins are mainly hosted by the Cretaceous Lepanto Metavolcanics basement rocks, with minor veins cutting the Pleistocene Imbanguila Dacite Pyroclastics. The mineral assemblages and homogenization temperatures of fluid inclusions indicate that the Carmen and Florence orebodies were deposited by fluids varying from high to very high sulfidation state. The enargite and QPG epithermal veins of Carmen and Florence cut porphyry‐type quartz veinlet stockworks and veins that host polyphase hypersaline fluid inclusions that did not homogenize at or below 400°C. These high‐temperature quartz exhibits distinctly different mineral chemistry from the quartz of the QPG and enargite‐rich epithermal veins. In particular, the Ti content of quartz of the porphyry‐type veinlet stockwork is elevated (>100 ppm), whereas the Ti concentration of the epithermal vein quartz crystals are below detection limits. The Fe concentration of quartz is high in epithermal vein quartz (>300 ppm), whereas nearly undetected in the porphyry‐type stockwork veinlet quartz. Multiple generations of quartz with different mineral chemistry, fluid inclusions morphology, temperature, salinity and bulk gas compositions, and stable isotopic ratios indicate the variable hydrothermal conditions throughout the mineralization history of the Mankayan District. The temperature, pH, sulfidation state, oxidation state, and fluid composition vary among the orebodies in Carmen and Florence areas. Furthermore, the characteristics of earlier alteration affected the apparent characteristics of subsequent mineralization. Abstract : This study documents the occurrence of several high‐sulfidation epithermal gold orebodies in the Mankayan Mineral District that overprinted earlier porphyry‐type mineralization. Multiple generations of quartz with varying mineral chemistry, fluid inclusions morphology, temperature, salinity and bulk gas compositions, and stable isotopic ratios, indicate the presence of different fluids throughout the mineralization in the Mankayan District.